Digital cephalometric analysis illustrating morphological variation of the soft palate - Tanya Khaitan; Ramaswamy Pachigolla; Ginjupally Uday; Praveen Kumar Balmuri; Sai Kiran Chennoju; Sreenivasulu Pattipati (Journal of Indian Academy of Oral Medicine and Radiology, 2015)
Introduction and Objectives: The soft palate plays a vital role in velopharyngeal closure which is strongly dependent on a close coordination of the velum and the contiguous pharyngeal structures. It is reasonable to hypothesize that these structures may have different characteristics to match up to different soft palate morphologies. Considering this, the present study was done to investigate the variation in the morphology of the soft palate. Materials and Methods: A total of 200 patients belonging to both the genders, in the age group 5-55 years, were selected from the outpatients visiting the Department of Oral Medicine and Radiology. All the study samples were subjected to lateral cephalogram and the morphology of the soft palate was categorized as described by You et al. Any additional finding was further differentiated as type 7 and so on. The length of soft palate was also evaluated using Sidexis next generation software. The data obtained were tabulated and subjected to statistical analysis. Results: The morphology of soft palate was categorized into eight types. Type 1 was the commonest type observed. The relationship between the different types of soft palate in various age groups was found to be non-significant. The mean length of the soft palate was found to be more in group V (46-55 years). The mean length of soft palate was found to be higher in males. There was a positive correlation between age and type of soft palate. Conclusion: The present study draws a new set of morphological classification for the soft palate.